Praktik Upcycling Sisa Tenun Sumba Timur menjadi Eco-fashion 4-in-1: Studi Praksis Sosial di Parahita Craft, Salatiga - Putri Rimba Widyawati; Arianti Ina Restiani Hunga; Rizki Amalia Yanuartha (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The fashion industry generates textile waste, creating an urgent need for more sustainable production and consumption practices. This study aims to examine the upcycling of East Sumba woven textile (Tenun Sumba Timur) remnants through the development of a 4-in-1 eco-fashion product at Parahita Craft and to analyze how habitus, capital, and the social field shape this practice. A qualitative case study approach was employed. Data were collected through participant observation during an internship, semi-structured interviews with eight informants, documentation, and document analysis. The data were analyzed using an interactive process of coding, theme development, data display, and conclusion drawing, and were interpreted through Pierre Bourdieu's theory of social practice. The findings show that upcycling is shaped by a culture of experimentation, knowledge of textile materials and sewing skills as forms of cultural capital, and institutional networks as social capital. The 4-in-1 product was developed through fabric classification, material combination, design discussions, and production testing. Among the three consumers interviewed, aesthetic appeal initially attracted interest, while cultural and sustainability narratives strengthened product recognition. However, this recognition did not automatically translate into market legitimacy or organizational economic independence. The study concludes that upcycling is a social practice shaped by the interaction of habitus, capital, and the social field.